Zonal migration and transport variations of the Kuroshio east of Taiwan induced by eddy impingements. (January 2018) - Chang, Ming-Huei; Jan, Sen; Mensah, Vigan; Andres, Magdalena; Rainville, Luc; Yang, Yiing Jang; Cheng, Yu-Hsin
Abstract: Variability of the Kuroshio east of Taiwan was observed at a cross-stream transect 50 km south of the PCM-1 line with an array of three moored ADCPs measuring for 23 months, supplemented with eleven repeated shipboard surveys. Observations of the Kuroshio's velocity structure reveal the absence of an obvious regular seasonal signal, but significant variability at 70–200 day period for both maximum velocity axis migration and transport due to interactions with mesoscale eddies. Empirical orthogonal function (EOF) analysis shows the migration and transport modes explain 46% and 29% of the total variance, respectively, which is in contrast to the findings at the PCM-1 line where the transport mode explained more variance than did the migration mode. The Kuroshio transport in the upper 500 m across a 150 km section is 17.2 Sv with a standard deviation of 5 Sv. The estimated Kuroshio transport is 4.3 Sv lower than that reported for the PCM-1 line, likely due to the interannual variations related to abundance of mesoscale eddies in the Subtropical Counter Current (STCC) region. Transport variability east of Taiwan is mostly caused by Kuroshio-eddy interactions. When single anticyclonic (cyclonic) eddies encounter the Kuroshio, they enhance (reduce) poleward transport, presumably by increasing (decreasing) the sea level anomaly (SLA) along the eastern flank of the Kuroshio (correlation = 0.82). When a pair of eddies impinges on the Kuroshio, the upstream confluence and diffluence caused by the dipole eddies increases and decreases the Kuroshio transport, respectively. Furthermore, the eastward (westward) currents that result from either the single eddy or the dipole eddy produce flow divergence (convergence) adjacent to the Kuroshio's eastern edge, favoring the offshore (onshore) migration of the Kuroshio axis. Highlights: Kuroshio strongly varies in migration and transport modes associated with eddies. Local barotropic/baroclinic responses and the upstream steering affect the transport. Flow divergence/convergence adjacent to the Kuroshio edge affects its axis.